EROS/fANATOS TENSION IN VALLEJO'S POETIC WORK: A HERMENEUTIGPSYCHOANALYTICAL STUDY - Vegas, irene (2008)
The tension between Eros and Tanatos, experimented as a unity, and expressed inVallejo's poetic texts with different modalities of representation, especially through theopposed pairs God/ Man, Mother/Son, Man/Woman, l/the Same, I /the Other, Resurrection/Tanatos is here analysed following Freud, Heidegger and Lacan.